STUDENTS’ ABILTY IN WRITING DESCRIPTIVE TEXTS FOR FIRST STUDENTS OF SIYASAH IN THE SYARIAH AND LAW FACULTY - Deasy Yunita Siregar (VISION, 2017)
Writing is an essential aspect of interaction on language teaching beside reading and speaking. Based on the ideas above, the researcher concludes that writing is a thinking process, a transaction with words followed by a physical act. The students are expected to be able to communicate in English both in oral and written form. Writing skill is very complex. It includes many things that are used as criteria. A good deal of attention is placed on compositions that students would emulate and how well a student final product measured up against a list of criteria that include content, organization, vocabulary use, grammatical use, and mechanical considerations such as spelling and punctuation